Computing functional urban areas using a hierarchical travel time approach - Moises Lenyn Obaco Alvarez; Vicente Royuela; Xavier Vítores (European Regional Science Association (ERSA), 2016)
We present a new approach to shape functional urban areas in terms of proximity. It uses travel time from urban cores to connect them and to determine its hinterland. It only needs information that nowadays it is available for most countries. In addition, we test this approach to a developing economy to show that it might be applied to the developing world. We compare it with commuting patterns, which is the common approach in literature. This might be a solution to identify functional areas in the developing world, where the characteristic is the lack of data to apply sophisticated methods. We also test internal migration and gravitational equation as proxies to define hinterland. We hope that this contribution helps to fill the gap at the time to work with developed and developing regions jointly, something impossible so far.
Keywords: R12; R14; R52; 330; Integrated cities; Ecuador; FUAs; Travel time